OPTIMALISASI PEMBELAJARAN MUATAN LOKAL UNTUK PRAKTIKUM PENERAPAN PADA ALAT PRINTER 3D DI SMKS MUHAMMADIYAH 1 KUBURAYA - Eko Julianto; Muhammad Iwan; Gunarto; Eko Sarwono; Yeyen Deaari Sandi (LPPM STAI Muhammadiyah Probolinggo, 2026)
This training activity on optimizing local content learning and 3D printer practical skills aims to improve participants' competence in project-based learning and basic digital manufacturing skills in vocational high school environments. The results of observation and evaluationshow an increase in participants' technical skills in operating the Anet A8 Plus 3D printer and Ultimaker Cura software, handle basic technical problems, and produce prototypes of adequate quality. In addition, this training encourages the development of participants' creativity in digital design and opens up opportunities for schools to develop local content and increase their independent production capacity in the creation of learning media and creative products. Based on these achievements, it is recommended that advanced training be conducted, focusing on advanced three-dimensional machine design and printing parameter optimization to produce more complex prototypes. Schools are also advised to add computer facilities and 3D printer devices and integrate three-dimensional printing technology into Merdeka Belajar-based learning modules. Sustained collaboration between universities and vocational high schools is deemed crucial to strengthen mentoring, enhance human resource competencies, and ensure consistent utilization of digital manufacturing technology at Muhammadiyah Vocational High School 1 Kubu Raya, Rasau Jaya District, West Kalimantan Province.